Narrative Polyphony Of Sting’s Album “Ten Summoner’s Tales” (1993) - Naumenko, Nataliia (My University, 2023)
У статті проаналізовано особливості оповідної структури альбому „Ten Summoner’s Tales” (1993), що його традиційно визнають як Magnum Opus Стінга. Загалом, незалежно від типу оповідача у творах Стінга, котрі складають альбом „Ten Summoner’s Tales”, елементи авторського світобачення та творчого досвіду органічно входять у пісенний текст, де вони набувають значення символів людського буття, оточених словесними образами і посилених музичним супроводом. The article analyses the specifications of narrative structures and types of narrators in the song lyrics from the album „Ten Summoner’s Tales” (1993), traditionally claimed the Magnum Opus of Sting. Overall, the various types of narrators in Sting’s lyrics composing „Ten Summoner’s Tales” bring the elements of the author’s own vital and creative experience into the song where they gain the generalized meanings as symbols of human life, being surrounded with verbal images and amplified with musical accompaniment.
Keywords: кафедра іноземних мов професійного спрямування; Стінг; пісня; музика; вірш; оповідь; ліричний герой; song; music; verse; narration; speaker